EDUKASI DAN SKRINING LABORATORIUM JAMUR SUPERFISIAL PADA SWAB SELA JARI TANGAN MASYARAKAT - Dita Artanti; Anindita Riesti Retno Arimurti; Yety Eka Sispita Sari; Fitrotin Azizah Fitrotin Azizah; Mulya Fitrah Juniawan; Ruspeni Daesusi; Nur Vita Purwaningsih; Tri Ade Saputro (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Superficial fungal infections remain a significant public health concern in tropical countries, including Indonesia. High humidity, intense physical activity, and inadequate personal hygiene increase the risk of fungal colonization on the skin, particularly in the interdigital spaces of the hands. Community education integrated with laboratory examination represents an effective preventive strategy to improve public awareness while enabling early detection of fungal colonization. This community service program aimed to improve participants' knowledge regarding the prevention of superficial fungal infections and to identify fungal colonization through interdigital hand swab examination. The activity was conducted at Yonif Kodam V/Brawijaya, Surabaya, in collaboration with the Bonek Bonita Surabaya community, involving 25 participants. Health education was delivered through interactive lectures and discussions covering risk factors, transmission, clinical manifestations, and preventive measures. Laboratory examination was performed using Sabouraud Dextrose Agar (SDA) culture followed by microscopic identification using 10% potassium hydroxide (KOH) preparation and Lactophenol Cotton Blue (LPCB) staining. Laboratory findings demonstrated fungal growth in 7 participants (28%), whereas 18 participants (72%) showed negative culture results. The isolated fungi were identified as Candida spp. and Aspergillus spp.. The educational intervention successfully enhanced participants' understanding of proper hand hygiene and the importance of early laboratory detection of superficial fungal infections. This collaborative program demonstrates that laboratory-based community education can serve as an effective model for promoting early detection and prevention of superficial fungal infections.